Examining Mathematics Learning Abilities as a Function of Socioeconomic Status, Achievement and Anxiety - Bernadett Svraka; Szilvia Ádám (MDPI AG, 2024)
Our mathematical thinking sheds light on how we see our world and what knowledge we have about it. In spite of this, mathematical performance is still mostly measured in calculation skills, and this also predestines the success of learning. So at school, what is important is how correctly we solved the task and not the way we got there. An internationally unique Hungarian-developed test (DPV-Pedagogical Examination of Dyscalculia/Diszkalkulia Pedagógiai Vizsgálata) draws our attention to the opposite of this. The special feature of the test is its criterion orientation, which emphasizes the correctness of mathematical thinking while examining the abilities necessary for learning mathematics. The aim of our study was to investigate, as a function of background variables (gender and socioeconomic status (SES)), (1) whether the abilities and thought processes required for learning mathematics function at an adequate level, (2) what effect these may have on mathematical performance, and (3) to what extent all of this is influenced by mathematical anxiety. Our background variables were gender and socioeconomic status. A total of 999 Hungarian students aged 10-15 participated in our study, including 483 boys and 516 girls. In general, we can say that the development of the skills necessary for learning mathematics is closely related to the students' performance. Nevertheless, it happens that we encounter low performance despite good skills. In several cases, we can experience the presence of anxiety, especially math anxiety, which in most cases, regardless of the level of abilities, negatively affects the success of math learning processes. The findings confirm that socioeconomic status, gender, and performance are risk factors for mathematical anxiety. The following hypotheses have been formulated along the lines of the research objectives set out in the abstract: There are no differences in ability and mathematical performance between boys and girls. Girls are more anxious when they have to solve a mathematical problem. Socioeconomic status predicts ability level and the presence of math anxiety. Mathematical anxiety (MA) modifies the validity of mathematical ability (DPV).